2016
DOI: 10.1161/hypertensionaha.116.07446
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence and Pentosidine Are Associated With Aortic Stiffening

Abstract: Abstract-Arterial stiffening, as characterized by an increase in carotid-femoral pulse-wave velocity or pulse pressure, increases the risk of cardiovascular disease, especially among individuals with type 2 diabetes mellitus. Advanced glycation end products are hypothesized to play a role in the development of arterial stiffness. Therefore, we investigated the association between skin autofluorescence, an estimate of tissue advanced glycation end products, and plasma advanced glycation end products on the one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 41 publications
2
50
2
1
Order By: Relevance
“…However, no association between intima-media thickness and MG-H1 or CRP could be found in these patients [59]. Lastly, an association between skin auto-fluorescence, pentosidine, and carotid-femoral pulse-wave velocity as a parameter of arterial stiffness, were more pronounced in individuals with diabetes mellitus type 2 than in healthy controls [60].…”
Section: Epidemiologic Studies On Cardiovascular Disease and Ages In mentioning
confidence: 71%
“…However, no association between intima-media thickness and MG-H1 or CRP could be found in these patients [59]. Lastly, an association between skin auto-fluorescence, pentosidine, and carotid-femoral pulse-wave velocity as a parameter of arterial stiffness, were more pronounced in individuals with diabetes mellitus type 2 than in healthy controls [60].…”
Section: Epidemiologic Studies On Cardiovascular Disease and Ages In mentioning
confidence: 71%
“…Elevated blood pressure may well be a consequence of increased AGE accumulation. A recent study demonstrated that carotid-femoral pulse-wave velocity and central pulse pressure were independently associated with plasma AGEs [43]. Several AGEs are able to form crosslinks within collagen in the vascular wall, which may result in impaired vascular elasticity and increased arterial stiffness, causing blood pressure to rise [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation is that proteinbound pentosidine may, better than the other AGEs in our analyses, reflect the tissue-AGE content. In that line, we previously reported that skin autofluorescence (a non-invasive measurement of skin AGE accumulation) and plasma protein-bound pentosidine were both positively associated with aortic stiffening, while protein-bound CML and CEL were not [38]. Plasma pentosidine also correlated with skin autofluorescence in Japanese haemodialysis patients [39].…”
Section: Discussionmentioning
confidence: 69%
“…For instance, MGO and GO may trigger distinct intracellular signals involved in various cellular functions in cultured endothelial cells, because of differences in their chemical structures [41]. The possibility of different contributions for AGEs in the development of vascular disease was also reported [38]. For instance, via binding to RAGE, AGEs like CML can activate inflammatory pathways (as reviewed in [42]), while cross-linking AGEs such as pentosidine may act via formation of cross-links between extracellular matrix proteins [43,44].…”
Section: Discussionmentioning
confidence: 98%